Immune Checkpoint Receptors Tim-3 and PD-1 Regulate Monocyte and T Lymphocyte Function in Septic Patients - Qi Xia; Li Wei; Yuntao Zhang; Jifang Sheng; Wei Wu; Yi Zhang (Mediators of Inflammation)
We aim to investigate the effects of Tim-3 and programmed cell death-1 (PD-1) on the monocytes and T lymphocytes in septic patients. Expression of Tim-3 and PD-1 on the CD3, CD4, and CD8 lymphocytes and monocytes was determined using flow cytometry. CBA technique was utilized to determine the expression of cytokines in the lymphocyte supernatant in addition to the IL-10 and TNF-α positivity in monocytes in the presence of Tim-3 and/or PD-1 receptor blockade. Compared with the normal control, significant elevation was observed in the expression of PD-1 on CD3 (P=0.004), CD4, and CD8 monocytes. Blockade of the Tim-3 signaling pathway contributed to the significant elevation of IL-10 and TNF-α in the supernatant of T lymphocytes in the septic patients, while the PD-1 signaling pathway blockade only triggered the obvious elevation of TNF-α in the T lymphocytes. Blockade of Tim-3 and PD-1 induced the positivity of IL-10- and TNF-α-expressing cells in the peripheral monocytes. Significant changes were noticed in the Tim-3 and PD-1 in the T lymphocytes and monocytes. Blockade of Tim-3 and PD-1 contributed to the function of lymphocytes and monocytes. In the septic process, Tim-3 and PD-1 played crucial roles in the immune response of T lymphocytes and monocytes.